Variable flow pipework systems - Parsloe, C. (CIBSE knowledge series ;, 2006)
This publication explains how to design re-circulating heating or cooling water systems incorporating variable speed pumps. Correctly designed, these systems have the potential to deliver worthwhile energy savings over the lifetime of a building. --